a) x+x+x= 6
b) 3*x+4=2*x+11
c)2*( x+3) =6
Răspunsuri la întrebare
Răspuns de
4
a. 3x=6⇒x=2;
b. 3x+4=2x+11⇒x=7;
c. 2x+6=6
⇒2x=0⇒x=0;
b. 3x+4=2x+11⇒x=7;
c. 2x+6=6
⇒2x=0⇒x=0;
Răspuns de
5
x + x + x = 6
3x = 6
x = 6 : 3
x = 2
b.
3 x + 4 = 2x + 11
3x - 2x = 11 - 4
x = 7
c.
2 x ( x +3 ) = 6
2 x 3 = 6
x + 3 = 3
x = 3- 3
x = 0
3x = 6
x = 6 : 3
x = 2
b.
3 x + 4 = 2x + 11
3x - 2x = 11 - 4
x = 7
c.
2 x ( x +3 ) = 6
2 x 3 = 6
x + 3 = 3
x = 3- 3
x = 0
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă